Community engagement for outbreak preparedness and response in high-income settings: A systematic review. Issue 7 (3rd July 2022) - Chiam, Ai Ling; Cheng, Ngan Wan Ivy; Larson, Heidi
ABSTRACT: Background: This review aims to (i) identify and critique existing methods of community engagement for outbreak preparedness and response in high-income settings, and (ii) understand community members' experiences of community engagement, and their views and concerns towards pandemic planning/response. Methods: Following the PRISMA guidelines, a systematic review was conducted by searching Medline, Embase, PubMed, Global Health, CINAHL Plus and Scopus for publications from 2004 to June 2019. Potential literature was screened using explicit inclusion and exclusion criteria. Included studies were appraised using the Critical Appraisal Skills Programme Qualitative Research checklist. Those using deliberative approaches were appraised using additional criteria for judging deliberation quality. Thematic synthesis was then conducted. Results: Primary studies employed participatory research approaches, deliberative forums, interviews/focus groups to engage community members on pandemic planning/response with varying degrees of involvement and methodological rigour. This review indicates such endeavours must take into account instrumental and relational considerations: socioeconomic pressures; agency and capacity; diversity and divergent views; educate, communicate and engage; trust and transparency. Conclusion: Community engagement for pandemic planning/response requires clear methods, processes and who 'community' constitutes. Instrumental and relational considerations must be addressed concurrently in pandemic planning/response to enhance preparedness for public health emergencies.